2015
DOI: 10.17338/trainology.4.1_19
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sodium bicarbonate supplementation on asoccer specific conditioning test in division III soccer players

Abstract: Objectives: This study investigated the performance enhancing effects of bicarbonate ingestion on soccer specific performance. Design: A randomized and double-blinded study. Methods: Division III collegiate male soccer players (N = 7) participated in the study. Participants ingested either an alkaline treatment (.3 g/kg NaHCO3) or placebo (cornflower) 60 min prior to exercise on two separate testing sessions spaced 7 days apart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Therefore, in total, 15 studies were included; 13 studies were published as full-text manuscripts in peer-reviewed journals, one study was published as a conference abstract, and one study is a part of a master's thesis. [4][5][6][7][8]13,15,16,[22][23][24][25][26][27][28] Eleven studies explored the effects of caffeine, whereas five studies examined the effects of sodium bicarbonate on Yo-Yo test performance (Table 1). One study included examined the isolated effects of both caffeine and sodium bicarbonate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in total, 15 studies were included; 13 studies were published as full-text manuscripts in peer-reviewed journals, one study was published as a conference abstract, and one study is a part of a master's thesis. [4][5][6][7][8]13,15,16,[22][23][24][25][26][27][28] Eleven studies explored the effects of caffeine, whereas five studies examined the effects of sodium bicarbonate on Yo-Yo test performance (Table 1). One study included examined the isolated effects of both caffeine and sodium bicarbonate.…”
Section: Resultsmentioning
confidence: 99%
“…3 The effects of caffeine and sodium bicarbonate have also been explored in the context of Yo-Yo test performance, with equivocal findings. [4][5][6][7][8] Some reported an increase in performance following the ingestion of either caffeine or sodium bicarbonate, while others report that performance in this test is unaffected by the use of these supplements. [4][5][6][7][8] Differences between the studies such as the dose, ingestion timing, and training status may explain some of these https://doi.org/10.1016/j.jsams.2019.08.016 1440-2440/© 2019 Sports Medicine Australia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computation of YYIR2 test global means, SDs and quantiles (Figure 3) involved 116 studies/subgroups reporting on 2,478 participants (median age = 23.2 years, IQR = 20.7–26.0 years) (Young et al, 2005; De Souza et al, 2006; Krustrup et al, 2006; Thomas et al, 2006; Mohr et al, 2007, 2016; Iaia et al, 2008, 2015, 2017; Morton et al, 2009; Rampinini et al, 2010; Rebelo et al, 2010; Thomassen et al, 2010; Christensen et al, 2011; Chuman et al, 2011; Mooney et al, 2011, 2013a,b; Roberts et al, 2011; Ueda et al, 2011; Gunnarsson et al, 2012; Ingebrigtsen et al, 2012, 2013, 2014; Nakamura et al, 2012; Saunders et al, 2012; Wells et al, 2012, 2014; Bassini et al, 2013; Buchheit et al, 2013; McGawley and Andersson, 2013; Mohr and Krustrup, 2013, 2014, 2016; Owen et al, 2013; Pivovarniček et al, 2013; Yuki et al, 2013; Fanchini et al, 2014; Karavelioglu et al, 2014; Lollo et al, 2014; Miloski et al, 2014; Nunes et al, 2014; Sampaio et al, 2014; Skovgaard et al, 2014; Brocherie et al, 2015a,b; Cholewa et al, 2015; Coelho et al, 2015; Gatterer et al, 2015; Hogarth et al, 2015a,b; Jamurtas et al, 2015; Krustrup and Mohr, 2015; Leme et al, 2015; Mara et al, 2015; Matta et al, 2015; McLean et al, 2015; Michalsik et al, 2015; Mohr, 2015; Rogan, 2015; Stein et al, 2015; Boer and Van Aswegen, 2016; Bouaziz et al, 2016; Chan et al, 2016; Inness et al, 2016; Joo, 2016; Kilit and Arslan, 2016; Lockie et al, 2016a,b,...…”
Section: Resultsmentioning
confidence: 99%
“…•kg −1 of NaHCO 3 extended the distance by 14% when the same exercise was performed. In addition, Jason[11] et al have presented that a distance extension of 12.4% was observed when 0.3 g of NaHCO 3 was ingested prior to the same exercise. These previous studies have shown the ergogenic effect of NaHCO 3 on high-intensity exercise state, which allows the performance of short-term, intermittent and anaerobic Yo-Yo IR2 under metabolic stress.…”
mentioning
confidence: 99%